Quantum Fourier Transform
Starting from this section, we demonstrate how to use QURI Parts to implement several algorithms containing quantum Fourier transform. We will cover:
Period finding
Phase estimation algorithm
The Shor's algorithm
So, in this section, we first illustrate how to use QURI Parts to build the circuit for performing quantum Fourier transform.
The purpose of this section is two fold:
Introduce how multi-controlled gate feature is used in practice.
Fix the convention of quantum Fourier transform.
The quantum Fourier transform is defined by the following operation:
∣ j ⟩ → QFT 1 2 n ∑ a = 0 2 n − 1 exp ( i 2 π a j 2 n ) ∣ a ⟩ , \begin{equation}
|j \rangle \xrightarrow{\text{QFT}} \frac{1}{\sqrt{2^n}}\sum_{a=0}^{2^n - 1} \exp \left(i\frac{2\pi a j }{2^n}\right) |a \rangle,
\end{equation} ∣ j ⟩ QFT 2 n 1 a = 0 ∑ 2 n − 1 exp ( i 2 n 2 πaj ) ∣ a ⟩ ,
where n n n is the number of qubits. Written in terms of binary number notation, the above equation becomes:
QFT ∣ j n − 1 ⋯ j 0 ⟩ = 1 2 n ∑ { a } exp ( 2 π i j × [ 0. a n − 1 ⋯ a 0 ] ) ∣ a n − 1 ⋯ a 0 ⟩ = 1 2 n ( ∣ 0 ⟩ + e 2 π i 0. j 0 ∣ 1 ⟩ ) ⊗ ( ∣ 0 ⟩ + e 2 π i 0. j 1 j 0 ∣ 1 ⟩ ) ⊗ ⋯ ⊗ ( ∣ 0 ⟩ + e 2 π i 0. j n − 1 ⋯ j 0 ∣ 1 ⟩ ) , \begin{equation}
\begin{split}
\text{QFT} |j_{n-1} \cdots j_0\rangle
&= \frac{1}{\sqrt{2^n}} \sum_{\{a\}} \exp\left(2\pi i j \times [0.a_{n-1}\cdots a_0] \right) | a_{n-1} \cdots a_0 \rangle\\
&= \frac{1}{\sqrt{2^n}}\left( |0\rangle + e^{2\pi i 0.j_0}|1\rangle \right) \otimes \left( |0\rangle + e^{2\pi i 0.j_1 j_0}|1\rangle \right) \otimes \cdots \otimes \left( |0\rangle + e^{2\pi i 0.j_{n-1}\cdots j_0}|1\rangle \right),
\end{split}
\end{equation} QFT ∣ j n − 1 ⋯ j 0 ⟩ = 2 n 1 { a } ∑ exp ( 2 πij × [ 0. a n − 1 ⋯ a 0 ] ) ∣ a n − 1 ⋯ a 0 ⟩ = 2 n 1 ( ∣0 ⟩ + e 2 πi 0. j 0 ∣1 ⟩ ) ⊗ ( ∣0 ⟩ + e 2 πi 0. j 1 j 0 ∣1 ⟩ ) ⊗ ⋯ ⊗ ( ∣0 ⟩ + e 2 πi 0. j n − 1 ⋯ j 0 ∣1 ⟩ ) ,
where j = j n − 1 ⋯ j 0 = ∑ i = 0 n − 1 j i 2 i j = j_{n-1}\cdots j_0= \sum_{i=0}^{n-1} j_i 2^i j = j n − 1 ⋯ j 0 = ∑ i = 0 n − 1 j i 2 i and a 2 n = 0. a n − 1 ⋯ a 0 = ∑ i = 0 n − 1 a i 2 i − n \dfrac{a}{2^n} = 0.a_{n-1}\cdots a_0 = \sum_{i=0}^{n-1} a_i 2^{i-n} 2 n a = 0. a n − 1 ⋯ a 0 = ∑ i = 0 n − 1 a i 2 i − n .
The last line of eq.(2) gives a convenient form where the circuit representation of the operation can be read out straightforwardly.
In our convention where the 0th qubit is positioned at the most right hand side, we need to first apply multiple SWAP gates to invert the order of the qubits:
∣ j n − 1 j n − 2 ⋯ j 1 j 0 ⟩ → SWAPs ∣ j 0 j 1 ⋯ j n − 2 j n − 1 ⟩ . \begin{equation}
|j_{n-1} j_{n-2} \cdots j_1 j_0 \rangle \xrightarrow{\text{SWAPs}} |j_{0} j_{1} \cdots j_{n-2} j_{n-1} \rangle.
\end{equation} ∣ j n − 1 j n − 2 ⋯ j 1 j 0 ⟩ SWAPs ∣ j 0 j 1 ⋯ j n − 2 j n − 1 ⟩ .
Then, we go through the standard textbook procedure of applying multiple controlled U1 gates to translate the above equation into the one in the second line of eq(2). For example, for the 0th qubit,
C U n − 1 , 0 ( n ) ⋯ C U 1 , 0 ( 2 ) H 0 ∣ j 0 j 1 ⋯ j n − 2 j n − 1 ⟩ = 1 2 C U n − 1 , 0 ( n ) ⋯ C U 1 , 0 ( 2 ) ∑ k = 0 1 e 2 π i k j n − 1 2 ∣ j 0 j 1 ⋯ j n − 2 k ⟩ = 1 2 C U n − 1 , 0 ( n ) ⋯ C U 2 , 0 ( 3 ) ∑ k = 0 1 e 2 π i k ( j n − 1 2 + j n − 2 2 2 ) ∣ j 0 j 1 ⋯ j n − 2 k ⟩ = ∣ j 0 j 1 ⋯ j n − 2 ⟩ ⊗ ∣ 0 ⟩ + e 2 π i ( 0. j n − 1 ⋯ j 0 ) ∣ 1 ⟩ 2 \begin{equation}
\begin{split}
&CU_{n-1, 0}(n) \cdots CU_{1, 0}(2) H_0|j_{0} j_{1} \cdots j_{n-2} j_{n-1} \rangle \\
=& \frac{1}{\sqrt{2}}CU_{n-1,0}(n) \cdots CU_{1, 0}(2) \sum_{k=0}^1 e^{2\pi i k\frac{ j_{n-1}}{2}}|j_{0} j_{1} \cdots j_{n-2} k \rangle \\
=& \frac{1}{\sqrt{2}}CU_{n-1,0}(n) \cdots CU_{2,0}(3) \sum_{k=0}^1 e^{2\pi i k (\frac{ j_{n-1}}{2} + \frac{ j_{n-2}}{2^2})}|j_{0} j_{1} \cdots j_{n-2} k \rangle \\
=& |j_{0} j_{1} \cdots j_{n-2}\rangle \otimes \frac{
|0\rangle + e^{2\pi i (0.j_{n-1} \cdots j_{0})}|1\rangle
}{\sqrt{2}}
\end{split}
\end{equation} = = = C U n − 1 , 0 ( n ) ⋯ C U 1 , 0 ( 2 ) H 0 ∣ j 0 j 1 ⋯ j n − 2 j n − 1 ⟩ 2 1 C U n − 1 , 0 ( n ) ⋯ C U 1 , 0 ( 2 ) k = 0 ∑ 1 e 2 πik 2 j n − 1 ∣ j 0 j 1 ⋯ j n − 2 k ⟩ 2 1 C U n − 1 , 0 ( n ) ⋯ C U 2 , 0 ( 3 ) k = 0 ∑ 1 e 2 πik ( 2 j n − 1 + 2 2 j n − 2 ) ∣ j 0 j 1